Design and experiment on differentially-driven microstrip antennas - Zhang, Yue Ping (2009)
Design and experiment is given of differentially-driven microstrip antennas. First, the design formulas to determine the patch dimensions and the location of the feed point for single-ended microstrip antennas are examined to design differentially-driven microstrip antennas. It is found that the patch length can still be designed using the formulas for the required resonant frequency but the patch width calculated by the formula usually needs to be widen to ensure the excitation of the fundamental mode using the probe feeds. The condition that links the patch width, the locations of the probe feeds, and the excitation of the fundamental mode is given. Second, the wideband techniques for single-ended microstrip antennas are evaluated for differentially-driven microstrip antennas. A novel H-slot is proposed for differentially-driven microstrip antennas to improve impedance bandwidth. Third, the effects of imperfect differential signal conditions on the performance of differentially-driven microstrip antennas are investigated for the first time. It is found that they only degrade the polarization purity in the H-plane with an increased radiation of cross-polarization. Finally, both differentially-driven and single-ended microstrip antennas were fabricated and measured. It is shown that the simulated and measured results are in acceptable agreement. More importantly, it is also shown that the differentially-driven microstrip antenna has wider impedance bandwidth of measured 4.1% and simulated 3.9% and higher gain of measured 4.2 dBi and simulated 3.7 dBi as compared with those of measured 1.9% and simulated 1.3% and gain of measured 1.2 dBi and simulated 1.2 dBi of the single-ended microstrip antenna.